Methodology for technical analysis to massify PV systems as an option for distributed energy generation in low-voltage systems (2015)
This work presents the results for the use of a methodology to predict in a statistically reliable way, the impact of the behavior in steady-state of the massification of Grid-connected photovoltaic system to a low-voltage system. The methodology can be implemented either in common using programming software or using any commercial electric system simulation software. First, a grid-connected photovoltaic model was determined and verified for comparing its behavior with output measured on a real installed system 3.6 kWp. Parallel, atmospheric parameters which affect the PV system's behavior were characterized in statistically way from actual measurements. The solar resource characterized and the photovoltaic system model are integrated in a non-deterministic approach using the stochastic method to estimate the electrical parameters in steady- state, describing the influence of massification of the Grid-connected PV systems in low-voltage grid. © 2015 IEEE.